Design, synthesis, and antitumor activity of novel benzoheterocycle derivatives as inhibitors of vascular endothelial growth factor receptor-2 tyrosine kinase. Issue 5 (May 2020) - Ding, Yangyang; Liu, Kai; Zhao, Xinyu; Lv, Yingtao; Yu, Rilei; Kang, Congmin
The vascular endothelial growth factor receptor-2 signaling pathway promotes the formation of new blood vessels, and vascular endothelial growth factor receptor-2 tyrosine kinase exists in both active and inactive conformations. Novel indole–benzimidazole and indole–benzothiazole derivatives joined by different linkers are designed and synthesized as inhibitors of vascular endothelial growth factor receptor-2 tyrosine kinase. All the synthesized compounds were evaluated for their cytotoxicity against four human cancer cell lines (HeLa, HT29, A549, and MDA-MB-435) and human umbilical vein endothelial cell. Meanwhile, the inhibitory activities against vascular endothelial growth factor receptor-2 are estimated in vitro and the binding interactions with dual conformations of vascular endothelial growth factor receptor-2 tyrosine kinase are evaluated by molecular docking. Compounds5a–c and14 show inhibitory activity against vascular endothelial growth factor receptor-2 tyrosine kinase and promising cytotoxicity, specifically with IC50 values ranging between 0.1 and 1 μM, which imply broad-spectrum antitumor activity. These results provide a deep insight into potential structural modifications for developing potent vascular endothelial growth factor receptor-2 tyrosine kinase inhibitors.